Human Psychology (fitrah) from Islamic Perspective - Ali Muhammad Bhat (International Journal of Nusantara Islam, 2016)
Education is crucial for all mankind. It is achieved to perfect all aspects of human’s life and to attain perfection in one’s life. To achieve true education, one must keep knowledge on the philosophy and objectives of education put forth by different religions and civilization but more importantly as stipulated in the Al-Quran and Sunnah. These sources help in the operative formulation of generating the complete growth of individual with integrated, balanced, and collective personality. The principal task of education is, to nurture the personal growth of a human being. It is through this development of the individual and the preservation and transmission of culture that both the individual and society attains a quality of life. A good man is not necessarily a complete man. No one can be stared as a complete human because there is no end to the growth of human personality. A wide knowledge of many subjects helps in the growth of personality (psychology) provided a man knows how to modify behavior and knows how knowledge and actions are integrated into a broad, total framework of life. This issue has been taken into hand to provide an insight from Islamic perspective for a broad continuum of personality development or what in contemporary era is called human psychology. An analytical approach is adopted to search the sources which contain information related to human nature in order to justify that religion has a strong voice to help humans to cognize the role of Islamic Psychology in human development.